Study on flow characteristics of natural gas containing CO2 invading wellbore during drilling - He, Haikang; Sun, Baojiang; Sun, Xiaohui; Li, Xuefeng; Shan, Zhengfeng (Frontiers in Physics, 2022)
The dissolution of the invaded gas in the drilling fluid during the drilling period leads to the increase of gas invasion concealment. It is of great significance for the development of acid gas reservoirs to clarify the solubility change and multiphase flow law in the annulus after the invasion of high CO2 containing natural gas. In this paper, considering the influence of gas solubility, the control equations of gas-liquid flow during drilling gas invasion are established. For the prediction of gas solubility, the interaction parameters of CH4 and water in the Peng and Robinson equation of state were optimized to establish a gas solubility prediction model. The solubility of natural gas with high CO2 content in water and brine solution was measured by phase equilibrium experiment. The results of the experiment and equation solution show that the newly optimized solubility model can accurately predict the solubility of CH4 and CO2 in water, and the prediction error is kept within 5%, and the prediction error for the solubility of CH4 and CO2 mixed gas is kept within 15%. Through the analysis of engineering drilling gas invasion examples, it is found that the increase of CO2 content in the invaded gas leads to the slow change of mud pit increment, and the farther the gas migration front is from the wellhead, the stronger the concealment. The gas solubility has a significant impact on the monitoring of gas invasion in low permeability reservoirs. The smaller the permeability is, all the invaded gas will be dissolved into the drilling fluid. With the migration to the wellhead, the gas will expand and release, and the sudden increase.